Unsilencing the Migratory Grief of International Students: A Conversation Starter to Support Asian International Students Through Family Loss - Ichikawa, Asuka (Journal of International Students, 2021)
This reflective essay explores the experience of international students’ migratory grief. Through a personal narrative, it describes the tendency among Asian international students to withhold help-seeking and transnational challenges that further complicate the grieving process among international students. Anticipating its relevance with the campus reopening during the COVID-19 pandemic, the article highlights the need for higher education institutions to foster an evidence-based and culturally-informed grief support.